The Making of a 3D-Printed, Cable-Driven, Single-Model, Lightweight Humanoid Robotic Hand - Tian, Li; Magnenat Thalmann, Nadia; Thalmann, Daniel; Zheng, Jianmin (Frontiers in Robotics and AI, 2017)
Dexterity robotic hands can (Cummings, 1996) greatly enhance the functionality of humanoid robots, but the making of such hands with not only human-like appearance but also the capability of performing the natural movement of social robots is a challenging problem. The first challenge is to create the hand’s articulated structure and the second challenge is to actuate it to move like a human hand. A robotic hand for humanoid robot should look and behave human-like. At the same time, it also needs to be light and cheap for widely-used purposes. We start with studying the biomechanical features of a human hand and propose a simplified mechanical model of robotic hands, which can achieve the important local motions of the hand. Then we use 3D modelling techniques to create a single interlocked hand model that integrates pin and ball joints to our hand model. Compared to other robotic hands, our design saves the time required for assembling and adjusting, which makes our robotic hand ready-to-use right after the 3D printing is completed. Finally, the actuation of the hand is realised by cables and motors. Based on this approach, we have designed a cost-effective, 3D printable, compact and lightweight robotic hand. Our robotic hand weighs 150 grams, has 15 joints which are similar to a real human hand and six Degree of Freedoms (DOFs). It is actuated by only six small size actuators. The wrist connecting part is also integrated into the hand model and could be customized for different robots such as Nadine robot(Magnenat Thalmann, Tian, & Yao, 2017). The compact servo bed can be hidden inside the Nadine robot’s sleeve and the whole robotic hand platform will not cause extra load to her arm as the total weight (150 grams robotic hand and 162 grams artificial skin) is almost the same as her previous unarticulated robotic hand which is 348 grams. The paper also shows our test results with and without silicon artificial hand skin, and on Nadine robot.